Vesical Imaging-Reporting and Data System (VI-RADS) for assessment of response to systemic therapy for bladder cancer: preliminary report - Pecoraro, Martina; Del Giudice, Francesco; Magliocca, Fabio; Simone, Giuseppe; Flammia, Simone; Leonardo, Costantino; Messina, Emanuele; De Berardinis, Ettore; Cortesi, Enrico; Panebianco, Valeria (Abdominal imaging, 2022)
Purpose The Vesical Imaging-Reporting and Data System (VI-RADS) criteria are expanding, providing fine differentiation of bladder wall layers involvement. We aimed to explore the feasibility of a novel categorical scoring, the Neoadjuvant chemotherapy VI-RADS (nacVI-RADS) for radiologic assessment of response (RaR), to define the spectrum of treatment response among patients with muscle invasive bladder cancer (MIBC). Methods Ten consecutive patients diagnosed with non-metastatic MIBC were prospectively enrolled and addressed to NAC and underwent mpMRI before staging resection and after the chemotherapy cycles. The follow-up MRI assessment was performed using the nacVI-RADS algorithm for evaluation of response to therapy. NacVI-RADS categorically define complete RaR, based on prior VI-RADS score, presence of residual disease, tumor size, and infiltration of the muscularis propria . Results NacVI-RADS categories were able to match all the final radical cystectomy pathology both for complete pT0 responders and for the patients defined as partial or minimal responders, who only showed some RaR inter-scoring class downstaging. Conclusion This report is the preliminary evidence of the feasibility of nacVI-RADS criteria. These findings might lead to possible paradigmatic shifts for cancer-specific survival risk assessment and to possibly drive the therapeutic decision through active surveillance programs, bladder-sparing modalities, or to the standard of care. Graphical abstract